The Implementation of the Connecting, Organizing, Reflecting, Extending (CORE) Learning Model is Integrated with the Problem Based Learning (PBL) Model to Enhance the Mathematical Problem-Solving Ability of PGSD Students - Nasution, Ismail Saleh; Nasution, Marah Doly; Sari, Suci Perwita (Indonesian Journal of Education and Mathematical Science, 2026)
This study aims to examine the effectiveness of the Connecting, Organizing, Reflecting, and Extending (CORE) learning model integrated with Problem Based Learning (PBL) in improving the mathematical problem-solving abilities of PGSD students. A quasi-experimental method with a non-equivalent control group pretest–posttest design was employed. The participants consisted of 62 fourth-semester PGSD students at Universitas Muhammadiyah Sumatera Utara in the 2024/2025 academic year, divided into an experimental group (n=32) and a control group (n=30). Research instruments included a mathematical problem-solving test, observation sheets, and reflective journals. Data analysis revealed a significant difference between the two groups, with the experimental group achieving a higher mean score (82.53) than the control group (71.67), supported by a t-value of 5.742 (p0.001). The N-gain results indicated a moderate improvement in the experimental group (0.58), exceeding that of the control group (0.31). Students in the experimental class demonstrated better performance across all problem-solving indicators, particularly in rechecking the solution process and results. Qualitative findings further showed improvements in conceptual understanding, strategic thinking, confidence, and collaboration. Overall, integrating CORE and PBL creates meaningful learning experiences and effectively enhances students’ mathematical problem-solving competence